Exploring the knowledge, perceptions and attitudes of the side effects of antiretroviral drugs amongst staff and HIV patients at public healthcare institutions in the Frances Baard District of the Northern Cape South Africa, 2012 - Herbert, Josephine Winley (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.